Influence of the concrete strength and the type of supports on the stress-strain state of a hyperbolie paraboloid shell foobridge structure - Luna Vargas, Sebastian Eduardo (2023)
Relevance. This work is the first in a series of publications on the selection of a suitable analytical surface for implementation as a self-supporting structure for a thin shell footbridge. The study on the influence of concrete strength, live load position and support types on the stress-strain state of a hyperbolic paraboloid (hypar) shell is presented. Objective - to define the initial design parameters such as the appropriate concrete strength and the support type that generates the best structural behaviour to perform the subsequent structural design of a thin shell footbridge. Methods. The static finite element analysis was performed for 4 compressive strengths of concrete (28, 40, 80, 120 MPa) which correspond normal, high and ultra-high resistance concrete, 5 different live load arrangements and 3 different support conditions. Results. The shell model with pinned (two-hinged) supports shows the same vertical displacements as the model with fixed supports (hingeless). For the studied shell thickness, in terms of stress behaviour, the model with pinned ends is more efficient. The combination of two-hinged supports with 80 MPa concrete strength shows a better structural performance.